High dose rate interstitial 192‐Ir brachytherapy for the treatment of a recurrent dermal vascular hamartoma in a horse. (24th October 2021) - Conti, F.; Poujet, L.; Delverdier, M.; Lallemand, E. A.; Benoit, J.
Summary: The successful application of an interstitial brachytherapy course is reported in a 14‐month‐old male Anglo European Studbook (AES) foal for the treatment of a recurrent dermal vascular hamartoma at the dorsal aspect of the pastern on the right hindlimb. The lesion was irradiated four times over 4 days to a total dose of 28 Gy. Progressive tumour shrinkage and necrosis were observed over 2 months. No significant acute side effect was reported at the end of the treatment, with excellent and long‐lasting cosmetic results observed. The only reported late effect was permanent leukotrichia within the treated area, which remained otherwise tumour‐free 1224 days after treatment. Results of this report suggest the potential use of radiation therapy (and specifically brachytherapy techniques), as an effective and safe treatment modality for vascular malformations in horses.